A new tetra-segmented splipalmivirus with divided RdRP domains from Cryphonectria naterciae, a fungus found on chestnut and cork oak trees in Europe - Sato, Yukiyo; Shahi, Sabitree; Telengech, Paul; Hisano, Sakae; Cornejo, Carolina; Rigling, Daniel; Kondo, Hideki; Suzuki, Nobuhiro (Virus research, 2022)
•A new splipalmivirus (CnSpV1) with divided RdRP was isolated from C. naterciae.•CnSpV1 has four (+)RNA genomic segments RNA1 to RNA4.•RNA1 and RNA2 encode divided RdRP motifs F, A and B, and C and D, respectively.•Protoplast fusion assay suggests an extremely narrow host range of CnSpV1. Positive-sense (+), single-stranded (ss) RNA viruses with divided RNA-dependent RNA polymerase (RdRP) domains have been reported from diverse filamentous ascomycetes since 2020. These viruses are termed splipalmiviruses or polynarnaviruses and have been characterized largely at the sequence level, but ill-defined biologically. Cryphonectria naterciae, from which only one virus has been reported, is an ascomycetous fungus potentially plant-pathogenic to chestnut and oak trees. We molecularly characterized multiple viruses in a single Portuguese isolate (C0614) of C. naterciae, taking a metatranscriptomic and conventional double-stranded RNA approach. Among them are a novel splipalmivirus (Cryphonectria naterciae splipalmivirus 1, CnSpV1) and a novel fusagravirus (Cryphonectria naterciae fusagravirus 1, CnFGV1). This study focused on the former virus. CnSpV1 has a tetra-segmented, (+)ssRNA genome (RNA1 to RNA4). As observed for other splipalmiviruses reported in 2020 and 2021, the RdRP domain is separately encoded by RNA1 (motifs F, A and B) and RNA2 (motifs C and D). A hypothetical protein encoded by the 5′-proximal open reading frame of RNA3 shows similarity to a counterpart conserved in some splipalmiviruses. The other RNA3-encoded protein and RNA4-encoded protein show no similarity with known proteins in a blastp search. The tetra-segment nature was confirmed by the conserved terminal sequences of the four CnSpV1 segments (RNA1 to RNA4) and their 100% coexistence in over 100 single conidial isolates tested. The experimental introduction of CnSpV1 along with CnFGV1 into a virus free strain C0754 of C. naterciae vegetatively incompatible with C0614 resulted in no phenotypic alteration, suggesting asymptomatic infection. The protoplast fusion assay indicates a considerably narrow host range of CnSpV1, restricted to the species C. naterciae and C. carpinicola. This study contributes to better understanding of the molecular and biological properties of this unique group of viruses.